Isolation, Identification and Risk Factors of Escherichia coli Bacteria in Dairy Goat's Milk Subclinical Mastitis in Siliragung District, Banyuwangi Regency - Lestari, Dewi Sri; Setiawan, Boedi; Saputro, Amung Logam; Mafruchati , Maslichah; Praja , Ratih Novita; Prastiya, Ragil Angga (Universitas Airlangga, 2023)
Mastitis is an inflammation of the mammary gland which can cause a decrease in milk production and income for farmers. Subclinical mastitis is mastitis without clinical symptoms but can result in a decrease in the quality of milk production. One of the main pathogens that cause mastitis is Escherichia coli. The risk factors for the occurrence of mastitis, both clinical and subclinical mastitis, can cause a decrease in milk production caused by several factors, including genetic, feed, and environmental factors. This study aims to determine the presence of subclinical mastitis in dairy goat milk in Siliragung District, Banyuwangi Regency. Sample testing was carried out at the SIKIA Instrument Laboratory, Airlangga University. Isolation was carried out using EMBA media (Eosin Methylene Blue Agar) for further identification consisting of Gram staining and biochemical tests. One of the biochemical tests used is the IMViC (Indole Methyl red Voges-Proskauer Citrate Test). The results of isolation, observation of characteristics, and identification of bacteria in the research that was carried out showed that 8% (5/62) of the samples tested were positively identified as Escherichia coli. The results showed that the risk factors for causing subclinical mastitis included cleaning the cage bedding, washing hands before milking, milking out, teat dipping, and medication.